Morphological Variations in Conidia of Arthrobotrys oligospora on Different Media - Singh, R. K. (The Korean Society of Mycology, 2005)
Most commonly occurring predacious fungus Arthrobotrys oligospora showed great variation in size and shape of conidia on some media. The formation of larger conidia was recorded on beef extract and nutrient agar media. The length of conidia in Richard's YPSS, Sabouraud's, PDA and corn meal agar media was of medium size while smaller conidia were produced on Czapek's, Jensen's, Martin's medium. Maximum width of conidia was recorded on YPSS medium followed by Sabouraud's medium. The average size of spores on nematode infested corn meal agar medium was slightly increased than those on corn meal agar medium.